A study of life internal rate of return - Sorrawee Roenganan (2022)
Life insurance, not included as a part of the legal obligation in some countries, is one of the investment approaches that might not stand high in the public favor for some people since this is a type of investments that the investor cannot know beforehand the exact return, and the returns completely depend on uncertainty of the policy specification in some circumstances. Similar to the other kinds of investment, investors in life insurance products have been seeking a tool for investment evaluation. However, currently there are no accurate tools that can provide the value of the investment in a life insurance product sensitive to the uncertainty. Internal rate of return is the basic tool that buyers or bankers may apply in order to find the rate of return of this type of investment. The investment decision tool is one of the most important keys that investors have utilized upon making their decisions on investments. Therefore, in this research, we propose a new mathematical model with applications for investment decision, being an extension of the internal rate of return by taking into account the life probability, considering different types of life insurance policies, and other factors specified on life insurance investments such as the premium, the death benefit, the maturity value, the sum insured, the lapse rate, the surrender value, the annuity certain, and the lapse rate with different genders and ages. This newly proposed model is named as the "Life Internal Rate of Return" or Life-IRR model. By using the sample data for both males and females aged 30 years old with expected benefit of 100,000 baht for different types of life insurance policies which are endowment plan, whole life plan and retirement plan, the results show that, for males, the highest life rate of returns is that obtained from the retirement plan (3.633692%), and the lowest life internal rates of returns is that obtained from the endowment plan (2.384443%), while the whole life plan offers moderate life rate of returns of 2.427941%. For females, the highest life rate of returns is that obtained from the retirement plan (3.335189%), and the lowest life internal rates of returns is that obtained from the whole life plan (2.104658%), while the endowment plan offers moderate life rate of returns of 2.308062%. The sensitivity analyses of the life internal rates of return perform the natural characteristics of life insurance.